2011
DOI: 10.1016/j.cognition.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Contextual modulation of reading rate for direct versus indirect speech quotations

Abstract: In human communication, direct speech (e.g., Mary said: "I'm hungry") is perceived to be more vivid than indirect speech (e.g., Mary said [that] she was hungry). However, the processing consequences of this distinction are largely unclear. In two experiments, participants were asked to either orally (Experiment 1) or silently (Experiment 2, eye-tracking) read written stories that contained either a direct speech or an indirect speech quotation. The context preceding those quotations described a situation that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
36
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 11 publications
(17 reference statements)
10
36
1
Order By: Relevance
“…Furthermore, split analyses of trials immediately preceding and immediately following "refresher" recordings of native and non-native speaker speech revealed that "speaker" effects weakened over time but then reappeared after exposure to another set of recordings (see online Supplemental Material). These results all support previous observations that APS of speech modulates reading processes (Kosslyn & Matt, 1977;Stites et al, 2013;Yao & Scheepers, 2011). The most important finding of the current study is that APS facilitated more syntactically driven, less good-enough processing of the sentences, as evidenced by higher response accuracy in the last two experiments under perceptual simulation conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, split analyses of trials immediately preceding and immediately following "refresher" recordings of native and non-native speaker speech revealed that "speaker" effects weakened over time but then reappeared after exposure to another set of recordings (see online Supplemental Material). These results all support previous observations that APS of speech modulates reading processes (Kosslyn & Matt, 1977;Stites et al, 2013;Yao & Scheepers, 2011). The most important finding of the current study is that APS facilitated more syntactically driven, less good-enough processing of the sentences, as evidenced by higher response accuracy in the last two experiments under perceptual simulation conditions.…”
Section: Discussionsupporting
confidence: 93%
“…David walked into the room and said quickly (slowly), "I finally found my car keys!" Yao and Scheepers (2011) used functional magnetic resonance imaging (fMRI) to show a significant boost in brain activity in auditory cortices as people read direct quotes. Assuming that the vast literature on "inner voice" cited above is not wrong, and that basic, default phonological and prosodic representations are indeed generated naturally during silent reading, the additional effects observed in these eye tracking and fMRI studies can be taken as evidence of an elaborated, prosodically richer representation-APS-which can be generated under certain circumstances.…”
mentioning
confidence: 99%
“…Inherent in this pre-lexical/post-lexical distinction is the notion that these post-lexical codes represent a more complete, speech-like phonological representation—the subjectively experienced inner voice (i.e., potentially representing full prosodic and intonational information), whereas the earlier, pre-lexical codes might be more abstract or impoverished (e.g., Eiter & Inhoff, 2008; Frost, 1998; Oppenheim & Dell, 2008). Indeed, there is evidence that the inner voice has aspects that are very speech-like, for example reflecting the speaking rate of the person who authored the text (e.g., Alexander & Nygaard, 2008; Kosslyn & Matt, 1977), and representing characteristics of a character's voice when reading dialogue (e.g., Kurby, Magliano, & Rapp, 2009; Yao & Scheepers, 2011). But again, there is substantial evidence for relatively rich, pre-lexical codes as well, which represent syllable information (e.g., Ashby, 2010; Ashby & Martin, 2008; Carreiras, Vergara, & Barber, 2005), vowel information (e.g., Abramson & Goldinger, 1997; Lukatela, Eaton, Sabadini, & Turvey, 2004), sub-phonemic information (e.g., voicing —Ashby et al, 2009), and reflect readers’ regional accents (Filik & Barber, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while the effect of implied talking speed on actual reading times may be a pervasive phenomenon, other aspects of the communicative situation [5], [6], such as a talker's voice or manner of speaking, may only be simulated under specific conditions. Together, our experiments paint a slightly complex, but coherent picture of the effect of direct and indirect speech quotations on comprehenders' mental representations.…”
Section: Discussionmentioning
confidence: 99%